Estrutura e funcionamento das paisagens da área de proteção ambiental do estuário do rio Curu/CE - Maria Rita Vidal; Abraão Levi dos Santos Mascarenhas (Confins)
This paper analyses the structure and operation of Protection Area (APA) landscapes in the Curu River Estuary, on the west coast of Ceará state, in Northeastern Brazil. The analysis was built on the theoretical and methodological basis of Landscape Geo- Ecology. The study showed that the APA landscape structure is composed of a mosaic of units moulded mainly by the influence of hydroclimatic factors that attribute distinct patterns to its set of features. The operational model designed shows the connections of landscapes with distinct hierarchical levels that are unified with the action of the lateral relationships. Finally, we present a theoretical model and an operational map that provides clarification of the mechanisms governing the functioning of the landscape under study.